The current state and historical developments of euthanasia legislation in Belgium and the Netherlands : A comparative legal analysis - Tuovinen, Henri (My University, 2024)
Euthanasia is a multidisciplinary issue concerning legislation, medical practise, politics, and ethics among other disciplines. The Netherlands and Belgium were the first two States in the world to legalize euthanasia, both enacting their Euthanasia Acts just a few months apart in 2002. In both States, euthanasia was already an existing medical practise at the time, meaning that the Euthanasia Acts did not in fact change the already ongoing euthanasia practices. This thesis compares the current-day euthanasia legislation of Belgium and the Netherlands as well as the historical developments leading to the current legislation. The study is mainly based on the historical and functional methods, aiming to understand the measures that each State has taken to address the issue of euthanasia regulation throughout the history of the euthanasia discussion. In the Netherlands, euthanasia was legalized after a series of court cases had formulated a set of criteria on acceptable euthanasia practices, and the criteria were adopted by the local prosecutors, meaning that carefully executed euthanasia cases would no longer be prosecuted or punished. In Belgium, on the other hand, euthanasia also existed as a common medical practise even before its legalization, but any case law on the subject does not exist. The unusual situation was due to the unwillingness to report or prosecute carefully executed euthanasia cases. As the case law did not exist in Belgium, euthanasia legislation was shaped in the parliament and was a mixture of political compromises and expert opinions and recommendations.

Eutanasia on monialainen tutkimuskohde, joka ulottuu muiden ohella ainakin lainsäädäännön, lääketieteellisen hoitokäytännön, politiikan ja etiikan osa-alueille. Hollanti ja Belgia olivat ensimmäiset eutanasian laillistaneet maat maailmassa, kumpikin sääti eutanasiaa säätelevän lakinsa vuonna 2002 vain muutaman kuukauden sisällä toisistaan. Eutanasia oli kuitenkin jo tuolloin vakiintunut osaksi hoitokäytäntöä kummassakin maassa, joten lakimuutoksilla ei ollut suurta vaikutusta todellisille, jo olemassa oleville eutanasiakäytännöille. Tämä opinnäytetyö vertailee Belgian ja Hollannin nykyistä eutanasialainsäädäntöä sekä niitä historiallisia kehityssuuntauksia, jotka johtivat eutanasian laillistamiseen ja nykyiseen oikeudelliseen tilaan. Työ perustuu historialliselle ja funktionaaliselle metodille, joiden avulla se pyrkii ymmärtämään niitä lainsäädännöllisiä keinoja, joita kumpikin valtio on käyttänyt eutanasian sääntelyyn sen historian aikana. Hollannissa eutanasia laíllistettiin oikeuskäytännön seurauksena, kun oikeuskäytännössä oli muodostunut kriteeristö hyväksyttäville eutanasiakäytännöille. Kriteeristö vakiintui käyttöön, kun syyttäjälaitos ryhtyi tekemään syyttämättäjättämispäätöksiä kriteereihin perustuen. Tämän seurauksena huolellisesti kriteerejä noudattaen tehtyjä eutanasiatapauksia vastaan ei enää nostettu syytteitä, eikä lääkäreitä rangaistu. Myös Belgiassa eutanasia oli vakiintunut osaksi yleistä hoitokäytäntöä jo ennen sen laillistamista. Hollannista poiketen Belgiasta ei kuitenkaan ole saatavilla eutanasiaa koskevaa oikeuskäytäntöä, vaan eutanasiatapaukset on pääsääntöisesti jätetty raportoimatta tai syyttämättä jo ennen käytännön laillistamista. Oikeuskäytännön puuttumisesta johtuen belgialainen eutanasialainsäädäntö on muodostunut poliitikkojen aloitteesta ja perustuu sisällöllisesti yhdistelmään poliittisia kompromisseja sekä asiantuntijalausuntoja.
Keywords: euthanasia, case law, eutanasia, oikeuskäytäntö